1998
DOI: 10.1074/jbc.273.47.31119
|View full text |Cite
|
Sign up to set email alerts
|

EDF-1, a Novel Gene Product Down-regulated in Human Endothelial Cell Differentiation

Abstract: Endothelial cell differentiation is a crucial step in angiogenesis. Here we report the identification of EDF-1, a novel gene product that is down-regulated when endothelial cells are induced to differentiate in vitro. The cDNA encoding EDF-1 was isolated by RNA fingerprinting from human endothelial cells exposed to human immunodeficiency virus type 1 Tat, a viral protein known to be angiogenic. The deduced amino acid sequence of EDF-1 encodes a basic intracellular protein of 148 amino acids that is homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…To obtain cDNAs representing mRNAs regulated by HGF in human endothelial cells, we utilized a modi®ed PCR-based di erential screening approach commonly referred to as RNA ®ngerprinting (Consalez et al, 1996;Dragoni et al, 1998). We obtained several di erentially expressed clones.…”
Section: Hgf Induces Tgf Bmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain cDNAs representing mRNAs regulated by HGF in human endothelial cells, we utilized a modi®ed PCR-based di erential screening approach commonly referred to as RNA ®ngerprinting (Consalez et al, 1996;Dragoni et al, 1998). We obtained several di erentially expressed clones.…”
Section: Hgf Induces Tgf Bmentioning
confidence: 99%
“…Several di erentially expressed genes were identi®ed. The bands corresponding to di erentially expressed genes were excised from the polyacrylamide gel, electroeluted, re-ampli®ed by PCR, cloned in Bluescript and sequenced as described (Consalez et al, 1996;Dragoni et al, 1998). Double-stranded sequence analysis was performed using the T7 Sequencing kit (Pharmacia) following the manufacturer's instruction.…”
Section: Rna ®Ngerprintingmentioning
confidence: 99%
See 1 more Smart Citation
“…The CpMBF1 transcription level is low in free sporozoites and intracellular parasites during their early invasion stages, and CpMBF1 protein is barely detectable in intact oocysts and free sporozoites, suggesting that CpMBF1 may play a role in activating certain genes during the intracellular development of C. parvum. In addition to the activation of histidine synthetic genes in yeast under histidine starvation, MBF1-mediated pathways are known to cause cell differentiation in insects, the formation of stalks in the slime mould Dictyostelium discoideum and the differentiation of endothelial cells in mammals (Dragoni et al, 1998;Kabe et al, 1999;Singleton et al, 1991;Takemaru et al, 1997). These observations, together with the parasite life cycle stage-dependent expression pattern, imply that CpMBF1 may be involved in the cell differentiation of C. parvum during its complex life cycle.…”
Section: Discussionmentioning
confidence: 75%
“…Drosophila nuclear receptor FTZ-F1 or yeast leucine zipper protein GCN4) (Dragoni et al, 1998;Kabe et al, 1999;Li et al, 1994;Liu et al, 2003;Takemaru et al, 1997Takemaru et al, , 1998. We have previously identified its C. parvum counterpart and demonstrated that the CpMBF1 gene is able to functionally complement MBF1 deficiency in yeast (Zhu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%